Perlindungan Hukum Investor Ritel dalam Perdagangan Aset Keuangan Digital Pasca POJK Nomor 23 Tahun 2025 - Mochammad Samsi Ridwan (SPT. haria Journal and Education Center Publishing, 2026)
The trading of digital financial assets, including crypto-assets, has undergone a significant regulatory shift following the transfer of supervisory authority from Bappebti to the Financial Services Authority (OJK). This transition was strengthened through OJK Regulation Number 27 of 2024 and further amended by OJK Regulation Number 23 of 2025, which expands the regulatory scope to include digital financial asset derivatives. This study aims to analyze the forms of legal protection available to retail investors in digital financial asset trading after OJK Regulation Number 23 of 2025 and to examine the regulatory weaknesses that still require further strengthening. This research employs a normative legal method using statutory, conceptual, and limited comparative approaches to international standards such as IOSCO, FSB, OECD, and MiCA. The findings show that legal protection for retail investors has been developed through licensing requirements, the legality of tradable assets, information disclosure, risk education, asset safeguarding, personal data protection, supervision of digital promotions, and complaint-handling and dispute-resolution mechanisms. However, the existing framework still contains weaknesses regarding platform liability standards, compensation mechanisms, client asset protection, supervision of derivative products, and effective recovery channels for retail investors. Therefore, regulatory strengthening should focus on more operational, measurable, and enforceable protection, ensuring that the OJK regime does not merely expand the legality of digital financial asset trading but also provides substantive protection for retail investors.